Interpreting interviews - Alvesson, Mats, 1956- (London : SAGE, 2011)
Researchers conducting interviews in the social sciences quickly find that there is no single best way to approach their task. This text offers a critique of traditional interviewing practices and provides a framework for thinking about issues such as trustworthiness, identity and language in a conceptual context.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social surveys -- Methodology; Interviewing -- Technique